Exploring simile implications in literary transcreation: a study of al-Manfaluti's al-'Abarat into English - Syed Abdullah, Syed Nurulakla; Abdullah, Muhammad Alif Redzuan; Mustapha, Nik Farhan; Irsan, Chandra (Persatuan Linguistik Malaysia, 2024)
This study examines the intricate procedure of translation and transcreation of Mustafa Lutfi al-Manfaluti's "Al-Abrat" into English, with a particular focus on the transcreation of Arabic similes. This analysis explores the intricate relationship between faithfulness to the original text and creative modification of the text to connect with English- speaking readers. The research sheds light on the difficulties and strategies of retaining the rhetorical complexity and cultural significance of the source text by examining 200 randomly selected similes from "Al-Abrat" The results demonstrate the crucial importance of cultural sensitivity and language proficiency in the process of literary transcreation. This emphasises the translator's dual obligation to both the original material and the cultural background of the target audience. This work enriches the field of translation studies by emphasising the need for a nuanced understanding of transcreation, especially in the field of literary translation from Arabic into English. There is a need for improved training programmes that equip translators with the skills to deal with the cultural subtleties, artistic qualities and linguistic difficulties inherent in the transcreation process. This research promotes a wider recognition of the potential of transcreation to connect different cultures, enhance intercultural understanding and strengthen the global literary repertoire.